Apparent water loss due to consumer meter inaccuracies in selected areas of South Africa - Couvelis, Frank Alan (Department of Civil Engineering, 2015)
Apparent losses form an important component of the International Water Association's water balance. While apparent losses look like real losses to a municipality, this is not actually the case. The main components of apparent losses are water meter under-registration and unauthorised consumption. Water utilities in South Africa and internationally are becoming increasingly aware of the importance of good meter management practices based on the vast amount of literature published and work done by municipalities in recent years. Water meters are known to increasingly under-register as they age and register consumption. They register consumption the least accurate at low flowrates and their accuracy in this range deteriorates the fastest. This study investigates the extent of the apparent loss problem in selected areas of South Africa due to meter inaccuracy in a number of different ways, including an inspection of new residential consumer meters, interrogation of a metering database, flow logging of domestic consumers with and without an Unmeasured Flow Reducer (UFR) installed and a compilation of reports on bulk consumer meters. It was found that 16 % of 402 properties investigated in the City of Cape Town had an on-site leakage and their median flowrate was 10 litres/ hour. In Bloemfontein, it was found that 28 % of the 167 properties investigated had an on-site leakage with a median flowrate of 20 l/h. An investigation into the performance of 15 mm positive displacement meters based on eThekwini's water meter database showed that the under-registration from these meters increase by 0.36 %-points per year and 0.9 %-points per 1000 kL registered. Flow logging of domestic consumers with and without UFRs, showed that there was no genuine improvement in meter accuracy with meters that had UFRs installed in-line with it. However, there were only 8 properties (3 of which having a UFR installed) in the study that were investigated and no statistical conclusive conclusions could be made. Bulk meter audits in Ekurhuleni and Tshwane showed apparent losses of 18 % and 19 % respectively.